ChatGPT: Improving Communication Efficiency and Business Management of MSMEs in the Digital Age - Frans Sudirjo; Abu Muna Almaududi Ausat; Syamsu Rijal; Yasir Riady; Suherlan Suherlan (Innovative: Journal Of Social Science Research, 2023)
The use of ICT has become an important requirement for all sectors, including MSMEs. Effective and efficient communication is critical to the success of MSMEs in competing in an increasingly tight and dynamic market through ChatGPT. This study aims to examine the potential of ChatGPT in improving the communication efficiency of MSMEs. The focus of this study is primarily qualitative. Methods for gathering information included paying close attention and taking detailed notes, with subsequent analysis included data reduction, visualization, and inference. The study arrived at the conclusion that the utilisation of artificial intelligence technologies such as ChatGPT can provide great benefits to MSMEs in improving communication efficiency and overall business management. In the growing digital era, the use of artificial intelligence technology can be a competitive advantage for MSMEs in developing their business.